KEPATUHAN PAJAK KENDARAAN BERMOTOR STUDI KOMPARASI SISTEM PAJAK MANUAL DAN DIGITAL - Linta Alafta Hamdi; Pancawati Hardiningsih (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2024)
Motor Vehicle Tax (MVT) receipts each year are followed by increased ownership of motor vehicles. The study aims to analyze and differentiate between two methods of manual and electronic tax payment, as well as the impact of the number of motor vehicles and unregistered vehicles. This method of research using quantitative samples purposive sampling obtained the number of samples of 36 data. This data source comes from secondary data, which is a summary of receipts of PKB (Motor Vehicle Tax) 2021-2023 received from the Samsat Office III Kota Semarang. According to the findings, the number of vehicles has a significant positive impact on the receipt of motor vehicle tax, vehicles that do not re-register have no significant impact on receiving motor vehicles tax, and there is a significant difference between manual and electronic tax payments on motor vehicle taxes. As for the advice related to this study, governments can provide a good understanding of the tax structures that are important for governments to manage and optimize income, encourage taxpayers to be more proactive, and provide advisory or training to the taxpayer on the urgency of payment of motor vehicle tax